2001
DOI: 10.1182/blood.v98.2.495
|View full text |Cite
|
Sign up to set email alerts
|

Expression of p15ink4b gene during megakaryocytic differentiation of normal and myelodysplastic hematopoietic progenitors

Abstract: In myelodysplastic syndrome (MDS), the expression of the cyclin-dependent kinase inhibitor p15 ink4B (p15) is frequently decreased because of the aberrant methylation of the gene promoter; p15 is normally up-regulated during megakaryocytic differentiation. It was hypothesized that p15 methylation and deregulation of gene expression contribute to defective megakaryocytopoiesis in patients with MDS. Here it is shown that the increasing autocrine production of TGF-␤1 stimulates megakaryocytic differentiation in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
1

Year Published

2002
2002
2008
2008

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 14 publications
3
25
0
1
Order By: Relevance
“…45 In contrast, less is known about the role of INK4 family members in endomitosis. One study revealed that p15 ink4b expression was up-regulated in CD41 ϩ cells generated ex vivo from human CD34 ϩ cells, 46 while another reported that p16 decreased upon megakaryocytic differentiation. 47 Our observation that GATA-1-deficient megakaryocytes express nearly 10-fold less p16 suggests that GATA-1 may directly repress p16 transcription in the course of megakaryocyte maturation.…”
Section: The Role and Regulation Of Cell-cycle Inhibitors In Endomitosismentioning
confidence: 99%
“…45 In contrast, less is known about the role of INK4 family members in endomitosis. One study revealed that p15 ink4b expression was up-regulated in CD41 ϩ cells generated ex vivo from human CD34 ϩ cells, 46 while another reported that p16 decreased upon megakaryocytic differentiation. 47 Our observation that GATA-1-deficient megakaryocytes express nearly 10-fold less p16 suggests that GATA-1 may directly repress p16 transcription in the course of megakaryocyte maturation.…”
Section: The Role and Regulation Of Cell-cycle Inhibitors In Endomitosismentioning
confidence: 99%
“…b-Actin was used in each PCR reaction as internal control according to the method previously described. 7,18 BM mononuclear cells and water were used, respectively, as positive and negative controls. PCR products were separated in 2% agarose gel and transferred onto nylon membranes (Amersham, Arlington Heights, IL, USA), and standard hybridization was performed using a p15-specific DNA probe.…”
Section: Dna Methylation Assaymentioning
confidence: 99%
“…However, methylated genes can be activated by the combination of HDACi and 5 Aza-2' deoxycytidine (Cameron et al, 1999). Genes known to be methylated in MDS and myeloid leukemia include the cell cycle inhibitor p15 INK4b , p16 and E-cadherin (Teo®li et al, 2001;Toyota et al, 2001). Hypermethylation of p15 and other key genes may contribute to the di erentiation block seen in MDS.…”
Section: Myelodysplastic Syndrome (Mds) Is a Candidate For DI Erentiamentioning
confidence: 99%